Relevansi penggunaan dangdut sebagai media efektif pengumpul massa kampanye pada pemilihan umum 2019 - Madonna, Metha; Dillah, Arya (Jurnal Komunikasi Profesional, 2020)
Abstract: The Presidential Election event in 2019 actually becomes a reflection of the establishment of the nation in democracy. General Election (Election) is the beginning of laying the foundation of the nation's democracy. Various campaign strategies are pursued by the success team, political parties and sympathizers of the Election contestants, including using dangdut music as an attraction for community gatherers (the masses).There is no accurate calculation about the mass of the campaign that gathered due to the appeal of dangdut with votes. But in fact the Golongan Karya (Golkar) is the party that first used dangdut in 1971 to be used as a campaign weapon. At that time Rhoma Irama, known as the King of Dangdut, attracted the attention of the masses. In 1977 Rhoma Irama succeeded in making the Partai Persatuan Pembangunan (PPP) defeat Golkar's dominance in Jakarta and Aceh.Result: music as a campaign media is very dominant as a means of entertainment and propaganda as well as attracting the masses in campaign. The use of dangdut as an effective media, mass campaign collectors show that it is still very relevant because people still like to watch dangdut directly despite political speeches. Even the two candidates for the Presidential Candidate (Capres) also used the dangdut and the most popular song to be used as the theme song as an identification song for the contestants.The results of interviews and data mining of key informants and informants from the 2019 presidential election success team, admitted that the use of dangdut music is still very relevant and strategic to gather the public to be moved consciously or unconsciously to attend a campaign activity. Dangdut music is also considered to be segmented or targeted specifically at certain layers of society, especially dangdut fans.Methodology: Descriptive qualitative quantitative paradigm research was carried out through surveys with direct observations in the field, the distribution of questionnaires was strengthened by interviews with mass of campaign participants as well as a number of informants such as political party figures, observers of political communication and people related to politics.Keywords: Relevance, Dangdut Music, Election Campaign